Sistem Informasi Pemesanan Paket Wisata di Kabupaten Bengkayang - Rahmi Hidayati; Irma Nirmala; Arif Rahmawan (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Bengkayang Regency is one of the regencies located in the West Kalimantan Province. Bengkayang Regency boasts numerous tourist destinations that can be visited. However, many people are still unaware of the tourist spots in Bengkayang. The purpose of the tourist package booking information system in Bengkayang Regency is to provide a platform that facilitates tourists in obtaining information and booking tour packages in the region. This system is built based on a website. The development stages of this system utilize a linear sequential model(waterfall). The system is accessible to both administrators and regular users. User accessible sections include information about tourist destinations, tour package selection, booking and confirmation, booking management, payment, and payment notifications. The tourist package booking information system in Bengkayang Regency can simplify the process for tourists to choose and book packages that meet their needs. System testing, conducted through black-box testing with predefined test cases, yielded results indicating that the system operates in accordance with requirements.